PENGARUH PERKAWINAN LINTAS AGAMA TERHADAP KEHIDUPAN RUMAH TANGGA - Tri Wahyuni (Nizham Jurnal Studi Keislaman, 2019)
All forms of interfaith marriage between Muslims and non-Muslims are not permitted, because all non-Muslims are polytheists, including ahl al-kitâb by some scholars afterwards; including al-Râzî and Sayyid Quutb. While some contemporary figures included in this group are scholars who are members of the Indonesian Ulema Council (MUI),Interfaith marriage between Muslims and non-Muslims is not prohibited, because all non-Muslims (now) are ahl al-kitâb. This opinion was expressed by Sayyid M. Rasyid Ridâ, and was followed by many contemporary thinkers; including in Indonesia.The opinion of the author is not in favor of one of the opinions above, but places ahl al-kitâb on a classification that distinguishes it from polytheism; with certain restrictions. So as not to regard all non-Muslims as ahl al-kitâb, or ahl al-kitâb as idolaters.